Sustainability Evaluation of 3D Concrete Printing in the U.A.E. Construction Projects - Hindieh, Mohammad (2023)
A Master of Science thesis in Construction Management by Mohammad Hindieh entitled, “Sustainability Evaluation of 3D Concrete Printing in the U.A.E. Construction Projects”, submitted in November 2023. Thesis advisor is Dr. Adil Kahwash Al-Tamimi and thesis co-advisor id Dr. Ghanim Kashwani. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).